A microstructure evaluation of different areas of resistance spot welding on ultra-high strength TRIP1100 steel. Issue 1 (1st January 2018) - Hajiannia, Iman; Shamanian, Morteza; Atapour, Masoud; Ghassemali, Ehsan; Ashiri, Rouholah
Abstract: In this study, the microstructure of resistance spot welds of advanced ultra-high strength TRIP1100 steel was investigated. For this purpose, welding was performed after determining the best welding parameters. Four sections of the heat-affected zone (HAZ) regions were selected in the regions where the heat exchange was used to control the microstructure. Then, they were used with EBSD by scanning electron microscopy (SEM). The results showed that the TRIP1100 steel microstructure consisted of polygonal ferrites, bainites, residual austenite (RA) and martensite/austenitic islands (M/A). They also showed that the melting zone (FZ) has a lath martensite structure, and the grains are larger in packets. The structure of the martensite and different orientation grains are located in the Upper-critical area (UCHAZ). In the inter-critical region (ICHAZ), the high carbon martensitic content is higher due to the presence and the structure of ferrite and martensite. In the sub-critical region (SCHAZ), due to the tempering of martensite at a temperature below AC1, the structure is similar to the base metal (BM), with the difference that the RA degradation reduces its structure by 50%. It was found that the RA in the BM had completely transformed. The results showed that with the movement of the BM to the weld metal, the boundaries with a low angle were increased.